2021
DOI: 10.1002/adma.202103056
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel Ionic Diodes toward Harvesting Ultralow‐Frequency Mechanical Energy

Abstract: Energy harvesting from human motion is regarded as a promising protocol for powering portable electronics, biomedical devices, and smart objects of the Internet of things. However, state‐of‐the‐art mechanical‐energy‐harvesting devices generally operate at frequencies (>10 Hz) well beyond human activity frequencies. Here, a hydrogel ionic diode formed by the layered structures of anionic and cationic ionomers in hydrogels is presented. As confirmed by finite element analysis, the underlying mechanism of the hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 43 publications
1
55
0
Order By: Relevance
“…The recti cation ratio (J+/J-, where J + and Jdenote the current density at forward and reverse bias) at ± 3.0 V is about 14 at 10 mV s − 1 (Fig. 2G), comparable to the ratio for previously reported two-dimensional counterparts (recti cation ratio ≈ 2 to 50) 34,35 . At the same time, SEBS-IM/SEBS-IM and SEBS-SN/SEBS-SN homojunction have no noticeable recti cation effect (Fig.…”
Section: Resultssupporting
confidence: 83%
“…The recti cation ratio (J+/J-, where J + and Jdenote the current density at forward and reverse bias) at ± 3.0 V is about 14 at 10 mV s − 1 (Fig. 2G), comparable to the ratio for previously reported two-dimensional counterparts (recti cation ratio ≈ 2 to 50) 34,35 . At the same time, SEBS-IM/SEBS-IM and SEBS-SN/SEBS-SN homojunction have no noticeable recti cation effect (Fig.…”
Section: Resultssupporting
confidence: 83%
“…This rectifying performance is superior than that of most ionic diodes reported in the previous literature, as summarized in Figure 2c where representative ionic diodes are compared. [1,20,22,[14][15][16][17][25][26][27][28][29]18,[30][31][32][33]19,[34][35][36][37][38] Note that the rectification ratios collected from these studies are the maximum values as claimed, and they were obtained under various ionic conditions and in different electric voltage ranges (detail information is listed in Table S2, Supporting Information).…”
Section: Working Principle Of the Flexible Ionic Diodementioning
confidence: 97%
“…Recently, type III diodes have been constructed from aqueous polyelectrolytes. One popular choice is to use PSS and PDAC as the polyanion and polycation respectively, with platinum foil as the electrode [171][172][173]. Carye et al and Zhang et al used these polymers directly while Wang et al embedded them in a double network.…”
Section: Diodesmentioning
confidence: 99%
“…Because the electrodes in these devices were made from platinum or silver and thus semipolarizable, the measured response of the diode was a function of the electrode interface in addition to the polyelectrolyte junction. For example, while the open circuit voltage of the system was likely in the hundreds of mV range [173], the device only conducted well in forward bias above 2 V when the platinum electrodes were able to split water efficiently [168]. Han et al made a similar type III diode with nonpolarizable electrodes and demonstrated a turn on voltage near 0 V [174].…”
Section: Diodesmentioning
confidence: 99%